Studies in the orthopteran fauna of Melanesia: New katydids of the tribe Agraeciini from Papua New Guinea (Orthoptera: Tettigoniidae: Conocephalinae) - Naskrecki, Piotr; Rentz, David C. F. (Zootaxa, 2010)
Two new genera (Ingrischia n. gen. and Pandanagraecia n. gen.) and 15 new forest species of Agraeciini (Orthoptera: Tettigoniidae) from New Britain and central Papua New Guinea are described: I. macrocephala n. sp., P. poregera n. sp., P. armata n. sp., P. bifurcata n. sp., P. stylata n. sp., Salomona richardsi n. sp., Pseudonicsara (P.) fascifrons n. sp., P. (P.) gugusu n. sp., Anthracites nakanaiensis n. sp., Gonatacanthus gahavisuka n. sp., Microsalomona sawetau n. sp., M. brachyptera n. sp., Scytocera smaragdifrons n. sp., Philmontis lobatus n. sp., and Trichophallus tricuspis n. sp. Stridulations of S. richardsi and S. godeffroyi (Pictet) are described.